NCOG-41. FUNCTIONAL OUTCOME FOLLOWING NON-DOMINANT HEMISPHERIC GLIOMA SURGERY FROM THE ASPECT OF INDEPENDENCE LEVEL, COGNITIVE FUNCTION AND RETURN TO SOCIAL LIVES - Nakajima, Riho (Neuro Oncol, 2020)
BACKGROUND: Functional outcome has been paid much attention in surgery for eloquent area or dominant hemisphere. Little is known about functional outcome following surgery for non-dominant hemispheric gliomas, although some resent reports revealed the importance of right cerebral hemisphere on glioma surgery. Here, we investigated functional outcome of right cerebral hemispheric gliomas from the aspect of independence level, cognitive function, and return to social lives. METHODS: Totally 82 patients with right cerebral hemispheric gliomas who underwent surgery for resection in Kanazawa university hospital were studied. Patients were divided into two groups, WHO grade II/III and IV. Karnofsky Performance Status (KPS), Mini-mental state examination (MMSE), and whether or not to return to work at pre-operation and chronic phase were evaluated. To reveal responsible region for decline of each index, the voxel-based lesion symptom (VLSM) analyses were performed. RESULTS: MMSE; no difference was found through postoperative course in grade II/III, whereas postoperative score of grade IV was declined significantly compared with pre-operation (25.1 and 21.9 point; p=0.048). KPS; preoperative independence level was maintained until chronic phase in grade II/III (94.7 and 89.5). While, in grade IV, postoperative KPS was declined significantly than that of pre-operation (82.0 and 70.0, p=0.007). Results of the VLSM analysis revealed that patients who resected temporo-parietal junction in grade IV showed significantly low KPS score. Return to social lives; Reintegration ratio of working population was 71% and 35% for grade II/III and IV, respectively. Of these, as for grade II/III gliomas, the cingulate cortex and medial orbito-frontal cortex relate to return to social lives. CONCLUSIONS: Functional outcome following surgery depends on tumor grade and resected region in right cerebral hemispheric gliomas.